Moving to the cloud : developing apps in the new world of cloud computing - Sitaram, Dinkar (Syngress, 2011)
Moving to the Cloud provides an in-depth introduction to cloud computing models, cloud platforms, application development paradigms, concepts and technologies. The authors particularly examine cloud platforms that are in use today. They also describe programming APIs and compare the technologies that underlie them. The basic foundations needed for developing both client-side and cloud-side applications covering compute/storage scaling, data parallelism, virtualization, MapReduce, RIA, SaaS and Mashups are covered. Approaches to address key challenges of a cloud infrastructure, such as scalability, availability, multi-tenancy, security and management are addressed. The book also lays out the key open issues and emerging cloud standards that will drive the continuing evolution of cloud computing. Includes complex case studies of cloud solutions by cloud experts from Yahoo!, Amazon, Microsoft, IBM, Adobe and HP Labs. Presents insights and techniques for creating compelling rich client applications that interact with cloud services. Demonstrates and distinguishes features of different cloud platforms using simple to complex API programming examples.